FOUR ESSAYS ON THE POLITICAL ECONOMY OF THE RENT OF NATURAL RESOURCES IN AFRICAN STATES - (:unkn) unknown (My University, 2018)
The main objective of this research is to show how the abundance of natural re-sources creates economic and political dysfunctions as ilustrated by African countries. This study is based on four essays. The first essay examines empirically about 36 African countries, the determinants of longevity in power. The second essay analyzes the effect of fragmentation in 45 African countries, with particular emphasis on political stability. The third essay deals with the effect of border disputes by conducting an empirical study of the DRC and its nine neigh-boring countries. Finally, the fourth essay focuses on the macroeconomic effects of the type of political regime in the DRC. We use several types of econometrics and data sources adapted to each of the situations mentioned. We achieve the following key results: (1) dependence on oil and minerals positively impacts longevity in power in Africa, and human capital reduces the chances for an African head of state to stay long in power. (2) fragmentation negatively impacts political stability. (3) the mining resource rents increase border conflicts in the DRC (4) The consequences of the type of political regime and the abundance of natural resources increase the macroeconomic instability in the DRC.We suggest that the promotion of the education sec-tor should be at the heart of government strategies and therefore a priority and the strengthe-ning of constitutional rules regarding elections.
Keywords: African Research